A volume integral approach for the modelling and design of HTS coils. Issue 4 (10th April 2019) - Statra, Yazid; Menana, Hocine; Belguerras, Lamia; Douine, Bruno
Abstract : Purpose: The purpose of this paper is to develop a rapid and realistic modelling approach for the design and characterization of high temperature superconducting (HTS) coils and windings carrying DC currents. Indeed, the strong dependence of the electromagnetic properties of such materials on the magnetic field makes the design and characterization of HTS systems a delicate operation where local quantities have to be evaluated. Design/methodology/approach: A volume integral modelling approach has been developed taking into account the electric nonlinearity of the HTS material which is represented by power law. The variations of the characteristic quantities of the HTS (critical current density and power law exponent) with the magnetic flux density are also taken into account by using Kim's law. The volume integral modelling allows to model only the active parts of the system and thus to overcome the difficulties linked to the multiscale dimensions. Findings: The model has been tested in a case study in which simulation results were compared to measurements and to finite element analysis. A good agreement was found which validates the model as a rapid and efficient tool for HTS coils and windings design and modelling. Practical implications: HTS coils are important elements of emerging superconducting devices which require a high level of reliability, such as generators or motors. The proposed approach is interesting to speed up the design and optimization procedures of such systems. Originality/value: Advanced structures of the basic elements have been used in the volume integral modelling, which results in a considerable gain in computation time and in memory-space saving while keeping a high level of precision and realism of the modelling, which has been verified experimentally.